(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article examines the main stages of the formation of aesthetic values of the younger generation of Kyrgyzstan on the example of the introduction of a single school uniform in educational institutions based on the ethnic and cultural characteristics of the region. Several conclusions have been drawn.